52nd Aerospace Sciences Meeting 2014
DOI: 10.2514/6.2014-0877
|View full text |Cite
|
Sign up to set email alerts
|

Resonant Interaction of a Rectangular Jet with a Flat-plate

Abstract: A resonant interaction between a large aspect ratio rectangular jet and a flat-plate is addressed in this experimental study. The plate is placed parallel to but away from the direct path of the jet. At high subsonic conditions and for certain relative locations of the plate, the resonance accompanied by an audible tone is encountered. The trends of the tone frequency variation exhibit some similarities to, but also marked differences from, corresponding trends of the well-known edgetone phenomenon. Under the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 17 publications
2
38
0
Order By: Relevance
“…(6.55) over the range |y 2 − y d | t d /2 and set (αD) 2 = 2.3 (where D is a characteristic length defined more precisely below) in order to fit the mean flow measurements of Zaman et al (2013). Figure 4, which is in qualitative agreement with experimental observations over the frequency range where amplification occurs, shows that the peak noise levels occur at fairly low Strouhal numbers and increase with increasing Ma.…”
Section: Final Formulasupporting
confidence: 73%
See 3 more Smart Citations
“…(6.55) over the range |y 2 − y d | t d /2 and set (αD) 2 = 2.3 (where D is a characteristic length defined more precisely below) in order to fit the mean flow measurements of Zaman et al (2013). Figure 4, which is in qualitative agreement with experimental observations over the frequency range where amplification occurs, shows that the peak noise levels occur at fairly low Strouhal numbers and increase with increasing Ma.…”
Section: Final Formulasupporting
confidence: 73%
“…As stated earlier, the model problem considered in this section can be used to represent the interaction between a jet emanating from a large-aspect-ratio rectangular nozzle with the trailing edge of a flat plate. Recent experiments on this configuration were performed at the NASA Glenn Research Center Zaman et al 2013). The relevant geometric parameters are shown in figure 5.…”
Section: Final Formulamentioning
confidence: 98%
See 2 more Smart Citations
“…Seiner and Manning [7] studied supersonic jet-plate flows from a supersonic rectangular nozzle, and they showed that the gap distance between the nozzle exit and plate surface was an important parameter with respect to the jet screech tone. Research has also shown that jet noise characteristics are influenced by the flat plate (flap) length [8][9]. In addition, the turbulence characteristics of such jet flows and their impact on jet noise have also been studied both numerically and experimentally [10].…”
Section: Introductionmentioning
confidence: 99%